(untitled) (Research, Society and Development, 2020)
The aim of the study was to evaluate the impact of processing by cooking in natura fruits on the content of bioactive compounds - vitamin C and ascorbic acid, phenolic compounds, flavonoids, carotenoids and anthocyanins, lycopene and β-carotene - and on antioxidant activity - DPPH and FRAP - of 9 varieties of commercial and non-commercial tomatoes. The fruits were harvested when they reached the point of physiological maturation, selected and evaluated in natura, and after grinding and cooking for 30 minutes. At the end of the experiment it was found that all bioactive compounds analyzed showed quantitative reductions when the fruits were processed, with cherry cultivars - 7, 8 and 9 - those that showed superior results compared to different bioactive compounds evaluated, proving to be interesting to be better explored. Regarding the antioxidant activities, the processed fruits of these cultivars showed less losses showing potential to be submitted to processing.